The four friends - N/A (N/A Mind to mind .)
Four friends$1 (Ba deer, a crow, a mouse, and a tortoise$1 (Blived in a forest and always helped each other. One day, the tortoise was caught by a hunter, but the other three worked together and saved him. Moral: True friendship and teamwork can overcome any problem.s
Keywords: English